Ultrafast Thermionic Electron Injection Effects on Exciton Formation Dynamics at a van der Waals Semiconductor/Metal Interface - Keller, Kilian R.; Rojas-Aedo, Ricardo; Zhang, Huiqin; Schweizer, Pirmin; Allerbeck, Jonas; Brida, Daniele; Jariwala, Deep; Maccaferri, Nicolò (ACS photonics, 2022)
Inorganic van der Waals bonded semiconductors such as transition metal dichalcogenides are the subject of intense research due to their electronic and optical properties which are promising for next-generation optoelectronic devices. In this context, understanding the carrier dynamics, as well as charge and energy transfer at the interface between metallic contacts and semiconductors, is crucial and yet quite unexplored. Here, we present an experimental study to measure the effect of mutual interaction between thermionically injected and directly excited carriers on the exciton formation dynamics in bulk WS2. By employing a pump–push–probe scheme, where a pump pulse induces thermionic injection of electrons from a gold substrate into the conduction band of the semiconductor, and another delayed push pulse that excites direct transitions in the WS2, we can isolate the two processes experimentally and thus correlate the mutual interaction with its effect on the ultrafast dynamics in WS2. The fast decay time constants extracted from the experiments show a decrease with an increasing ratio between the injected and directly excited charge carriers, thus disclosing the impact of thermionic electron injection on the exciton formation dynamics. Our findings might offer a new vibrant direction for the integration of photonics and electronics, especially in active and photodetection devices, and, more in general, in upcoming all-optical nanotechnologies.